Continuous spinal analgesia with levobupivacaine for postoperative pain management: Comparison of 0.125% versus 0.0625% in elective total knee and hip replacement: A double-blind randomized study - Alessandro D'Ambrosio; Savino Spadaro; Chiara Natale; Antonella Cotoia; Michele Dambrosio; Gilda Cinnella (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Continuous spinal anesthesia (CSA) has not been widely used for postoperative analgesia, mainly to avoid complications from the subarachnoid injection. Recently, the introduction of low caliber CSA catheters (Spinocath ® ), has allowed to decrease anesthetics doses and volumes with good analgesia and reduced complications. The aim of this present study was to compare two concentrations of levobupivacaine administered through CSA for postoperative pain management after major orthopedic surgery. Secondary outcomes were adverse events associated with CSA. Material and Methods: Thirty-two patients were randomized to receive sufentanil 1 mcg/h plus levobupivacaine 0.125%-1 ml/h (Group A 0.125 ) or 0.0625%-2 ml/h (Group B 0.0625 ) for postoperative analgesia through CSA catheter, connected to the elastomeric pump over 48 h. The quality of analgesia was assessed based on pain intensity by Visual Analogic Scale (VAS). Sensory and motor function, hemodynamic, and respiratory parameters were recorded for 96 h after surgery, after which the catheter was removed. In addition, joint mobility was assessed, and any side effects were noted. Results: VAS score was ≤30 mm in 25 patients. Three patients in Group A 0.125 and 4 in Group B 0.0625 (NS), received a rescue dose of levobupivacaine. Median VAS in Group A 0.125 was lower than in Group B 0.0625 on T 1 h (8 ± 11 vs 16 ± 11; P < 0.05), and on T 4 h (11 ± 8 vs 18 ± 1; P < 0.05). All patients remained hemodynamically stable. There were no significant differences between groups for postoperative joints mobility. Conclusion: Levobupivacaine at a dose of 1.25 mg/h administered by CSA provides good quality analgesia independent of concentration and solution volume in patients undergoing total knee and hip replacement.